State of the Art in Idiopathic Pulmonary Fibrosis - Wygrecka, Malgorzata; El Agha, Elie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a compilation of ten publications, including original-research and review articles, and the accompanying editorial within the scope of a Special Issue entitled: "State of the Art in Idiopathic Pulmonary Fibrosis" published in Cells.